2010
DOI: 10.2527/jas.2009-2512
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nutrient restriction of bovine dams during early gestation on postnatal growth, carcass and organ characteristics, and gene expression in adipose tissue and muscle1

Abstract: Angus x Hereford heifers (15 mo and artificially inseminated to a single sire) were used to evaluate the effect of prenatal nutritional restriction on postnatal growth and development. At d 32 of gestation, dams were stratified by BW and BCS and allotted to a low-nutrition [55% of NRC (1996) requirements, n = 10] or moderate-nutrition [100% of NRC (1996) requirements, n = 10] diet. After 83 d of feeding, dams were commingled and received a diet in excess of requirements. Dams were allowed to calve naturally, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
65
2
9

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(88 citation statements)
references
References 41 publications
12
65
2
9
Order By: Relevance
“…Nevertheless, even though differences in organ cellular composition and function were noted, Long et al (2009Long et al ( , 2010b showed that when beef cows are provided nutrients at a level that meets nutritional requirements during late gestation, it can ameliorate many of the negative consequences (growth and carcass characteristics) of intrauterine growth restriction resulting from early-to midgestational nutrient restriction. Also, other research with late-gestational supplementation of cows has resulted in positive effects on age at puberty and pregnancy rate of female offspring (Martin et al, 2007;Funston et al, 2010).…”
Section: Calf Performancementioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, even though differences in organ cellular composition and function were noted, Long et al (2009Long et al ( , 2010b showed that when beef cows are provided nutrients at a level that meets nutritional requirements during late gestation, it can ameliorate many of the negative consequences (growth and carcass characteristics) of intrauterine growth restriction resulting from early-to midgestational nutrient restriction. Also, other research with late-gestational supplementation of cows has resulted in positive effects on age at puberty and pregnancy rate of female offspring (Martin et al, 2007;Funston et al, 2010).…”
Section: Calf Performancementioning
confidence: 99%
“…Prior research has shown that nutrient restriction during early to mid-gestation negatively affects fetal growth (Wu et al, 2004), including myogenesis and adipogensis (Du et al, , 2011, decreases tenderness and adipose tissue deposition , decreases the responsiveness of the hypothalamic-pituitary-adrenal axis in female progeny (Long et al, 2010a), organ development and function (Long et al, 2009), and gene expression (Long et al, 2010b). Nevertheless, even though differences in organ cellular composition and function were noted, Long et al (2009Long et al ( , 2010b showed that when beef cows are provided nutrients at a level that meets nutritional requirements during late gestation, it can ameliorate many of the negative consequences (growth and carcass characteristics) of intrauterine growth restriction resulting from early-to midgestational nutrient restriction.…”
Section: Calf Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Variations in nutrient intake alters the mass (Long et al, 2010) and cellularity (Caton et al, 2009) of visceral tissues which are among the most metabolically active in the body of ruminants (Ortigues and Doreau, 1995). Visceral tissues can account for up to 50% of total energy expenditure (Burrin et al, 1989), divided almost equally between the digestive tract and the liver.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to farm animals, the effects of maternal undernutrition during gestation on performance and/or body composition of the offsprings has been extensively studied in sheep (Krausgrill et al, 1999;Fahey et al, 2005;Zhu et al, 2006;Daniel et al, 2007), pigs (Bee, 2004;Gondret et al, 2005;Rehfeldt and Kuhn, 2006) and cattle (Long et al, 2010;Robinson et al, 2013). In rabbits, feed restriction in late pregnancy may alter mortality rate and birth-to-weaning weights (Nafeaa et al, 2011), although the timing of feed restriction is likely important for reproductive performance (Manal et al, 2010).…”
Section: Introductionmentioning
confidence: 99%